Automated Translation Preference with a Bilingual Chatbot - Park, Mina; Aiken, Milam (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
Free, online language translation services are being used by people around to the world to facilitate communication. However, it takes time and effort for a person to load the Web page in a browser, copy and paste text into the site, and translate words. The process quickly becomes tiresome. Instead, some computer programs are providing automated translation. However, no studies have been conducted to determine the efficiency or effectiveness of such an approach. In this study, we compare how students used an English-based chatbot with and without German automatic translation. Results show that students took nearly 1.5 times longer than their stated upper time limit to manually translate. In contrast, the automated translation was at least 30 times faster. In addition, the students were significantly more satisfied with the automated than the manual system.